PENGARUH HARGA DAN CITRA MEREK TERHADAP MINAT BELI THRIFTING SHOP DI KALANGAN MAHASISWA AKTIF JURUSAN PENDIDIKAN EKONOMI - Muhammad Firdaus Haby Ash Shidiqy; Septyan Budy Cahya (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This study aims to determine the effect of price and brand image on thrifting buying interest among active students of economic education at Surabaya State University. The sample used was 92 students, selected using a simple random sampling technique. The data analysis technique uses multiple linear regression. The research results explain that partially one of the variables has no effect on the independent variable, namely the price variable (X1), while the brand image variable has an effect on purchase intention. As well as the results of the study explain that simultaneously there is an influence of price and brand image on the intention to buy Thrifting shop.